The Effect of Arabic Extracurricular Activities Using the “Numbered Head Together” Method to Improve Speaking and Writing Skills in the Nour Al-Hidayah Al-Falah Vocational High School | تأثير أنشطة اللامنهجية العربية باستخدام طريقة “Numbered Head Together’’ لترقية مهارة الكلام والكتابة في المدرسة العالية المهنية نور الهداية الفلاح - Sholikhah, Anik Indrawati; Zainuddin, Ammar; Fuadi, Abdul Hafizh Nur (An-nahdloh : Journal of Arabic Teaching, 2023)
This research was motivated by the fact that Arabic language learning was only carried out during extra-curricular activities. The many obstacles faced require serious handling in improving Arabic language skills and the Numbered Head Together (NHT) method as a supporting solution. This research is a quantitative research with a pre-experimental research design. From the data obtained, it is known that the use of the NHT method is to improve speaking and writing skills. The average Pretest was 70.22 and Posttest was 78.48. The results obtained showed an increase of 82.6 or was called effective. So with this, future research might be able to add one more skill to be tested using the NHT method.